Enhancing numeracy literacy in embryology: Validity and practicality of augmented reality media for gametogenesis - M. Arsyad; Muhammad Zaini; Amalia Rezeki; Ika Wardani; Muhammad Iqbal Trinajah; Muhammad Aldy Nurrachman (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Augmented reality (AR) offers immersive visualization that can transform learning of abstract biological processes. Yet, its pedagogical integration with mathematical thinking in higher education remains limited. This study developed AR media for gametogenesis to enhance students’ numeracy literacy. Integrating mathematical thinking into AR media is essential to strengthen students’ ability to interpret biological data quantitatively. According to OECD’s PISA results, Indonesia’s mathematics score (366) remains below the global average (472), consistent with findings showing that most students’ literacy levels fall within low to moderate categories. This study is a development research using a descriptive quantitative approach adapted from the Lee & Owens model. AR gametogenesis media were developed using Blender and Assemblr EDU, featuring spermatogenesis content and numeracy exercises based on six numeracy literacy indicators. Validation was conducted by three experts (content, language, and media), and practicality testing involved 14 Biology Education students from Lambung Mangkurat University. Data were analyzed using validity and practicality formulas. Results indicated that the media achieved “very valid” ratings in content, presentation, and graphics, and was considered practical in design, ease of use, and usefulness. Therefore, the AR gametogenesis media integrated with mathematical thinking is valid, practical, and beneficial for improving Biology Education students’ numeracy literacy.Abstrak. Augmented reality (AR) menawarkan visualisasi imersif yang dapat mengubah pembelajaran proses biologis yang abstrak. Namun, integrasi pedagogisnya dengan berpikir matematis dalam pendidikan tinggi masih terbatas. Penelitian ini bertujuan mengembangkan media AR untuk gametogenesis untuk meningkatkan literasi numerasi siswa. Mengintegrasikan berpikir matematis ke dalam media AR sangat penting untuk memperkuat kemampuan siswa dalam menafsirkan data biologis secara kuantitatif. Menurut hasil PISA OECD, skor matematika Indonesia (366) masih di bawah rata-rata global (472), konsisten dengan temuan yang menunjukkan bahwa sebagian besar tingkat literasi siswa berada dalam kategori rendah hingga sedang. Penelitian ini merupakan penelitian pengembangan dengan menggunakan pendekatan kuantitatif deskriptif yang diadaptasi dari model Lee & Owens. Media gametogenesis AR dikembangkan menggunakan Blender dan Assemblr EDU, yang menampilkan konten spermatogenesis dan latihan numerasi berdasarkan enam indikator literasi numerasi. Validasi dilakukan oleh tiga ahli (konten, bahasa, dan media), dan uji praktikalitas melibatkan 14 mahasiswa Pendidikan Biologi dari Universitas Lambung Mangkurat. Data dianalisis menggunakan rumus validitas dan praktikalitas. Hasil penelitian menunjukkan bahwa media tersebut mencapai peringkat "sangat valid" dalam hal konten, presentasi, dan grafis, serta dinilai praktis dalam hal desain, kemudahan penggunaan, dan kegunaan. Oleh karena itu, media gametogenesis AR yang terintegrasi dengan pemikiran matematika valid, praktis, dan bermanfaat untuk meningkatkan literasi numerasi mahasiswa Pendidikan Biologi.